Robots Incorporated. - Cherry, S.
Software pundits and tech analysts can be forgiven for overlooking Microsoft's new robotics group. Right now, the robotics world is rife with devices that don't easily work together or with standard programming tools. Good robotics programming is far harder than writing a typical application for personal computers. Each component is expected to act autonomously and react to complicated events in the world of a kind that a printer or mouse never has to deal with.
Keywords: Robotics programming